2018
DOI: 10.1111/jam.14061
|View full text |Cite
|
Sign up to set email alerts
|

Metal-ion-induced expression of gene fragments from subseafloor micro-organisms in the Kumano forearc basin, Nankai Trough

Abstract: We successfully linked gene-induction response with sequence information for gene fragments of previously unknown function. The SIGEX-based approach exhibited the potential to identify genetic function in unknown gene pools from the deep subseafloor biosphere, as well as novel genetic components for future biotechnological applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 59 publications
0
7
2
Order By: Relevance
“…The insert length (0.8–8 kbp) was confirmed by restriction enzyme digestion ( Eco RI/ Hin dIII) of plasmids from randomly selected 56 clones (28 clones from each library). The sum length of DNA inserts (approximately 6 Gbp for both libraries) exceeded that of our previous attempts (0.05 Gbp) ( Futagami et al, 2013 ; Wakamatsu et al, 2018 ), and those reported by Uchiyama et al (2005) , Uchiyama and Watanabe (2008) , Uchiyama and Miyazaki (2013) , (0.1 Gbp) and by Meier et al (2016) (1 Gbp).…”
Section: Resultscontrasting
confidence: 61%
See 4 more Smart Citations
“…The insert length (0.8–8 kbp) was confirmed by restriction enzyme digestion ( Eco RI/ Hin dIII) of plasmids from randomly selected 56 clones (28 clones from each library). The sum length of DNA inserts (approximately 6 Gbp for both libraries) exceeded that of our previous attempts (0.05 Gbp) ( Futagami et al, 2013 ; Wakamatsu et al, 2018 ), and those reported by Uchiyama et al (2005) , Uchiyama and Watanabe (2008) , Uchiyama and Miyazaki (2013) , (0.1 Gbp) and by Meier et al (2016) (1 Gbp).…”
Section: Resultscontrasting
confidence: 61%
“…The next optimization step concerned the DNA size selection, which is the most important step in plasmid library preparation. In previous reports, inserted DNA was size-selected by electrophoresis and gel excision ( Futagami et al, 2013 ; Wakamatsu et al, 2018 ). Although a TOPO-vector with a dT-overhang at its 3′ end was used in the above-mentioned studies, clones with green fluorescence, which indicated that no DNA insert was introduced into the plasmid, were frequently observed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations